2010
DOI: 10.1111/j.1438-8677.2010.00385.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic analyses of plant water relocation using deuterium as tracer – reduced water flux of Arabidopsis pip2 aquaporin knockout mutants

Abstract: Due to reduced evaporation and diffusion of water molecules containing heavier isotopes, leaf water possesses an elevated (18)O or (2)H steady-state content. This enrichment has been exploited in plant physiology and ecology to assess transpiration and leaf water relations. In contrast to these studies, in this work the (2)H content of the medium of hydroponically grown Arabidopsis thaliana was artificially raised, and the kinetics of (2)H increase in the aerial parts recorded during a short phase of 6-8 h, un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 61 publications
1
31
1
Order By: Relevance
“…These data suggest a model whereby the stomatal closing response to ABA involves an increase in guard cell water permeability mediated by PIP2;1. This function adds to previously described roles of PIP2;1 in root and leaf vein water transport (Da Ines et al, 2010;Péret et al, 2012;Prado et al, 2013) and lateral root emergence (Péret et al, 2012).…”
Section: Genetics Of Guard Cell Aquaporinsmentioning
confidence: 76%
See 1 more Smart Citation
“…These data suggest a model whereby the stomatal closing response to ABA involves an increase in guard cell water permeability mediated by PIP2;1. This function adds to previously described roles of PIP2;1 in root and leaf vein water transport (Da Ines et al, 2010;Péret et al, 2012;Prado et al, 2013) and lateral root emergence (Péret et al, 2012).…”
Section: Genetics Of Guard Cell Aquaporinsmentioning
confidence: 76%
“…The pip2;1-1 and pip2;1-2 knockout mutants and the two complemented lines, pip2;1-1 PIP2;1 and d35S:PIP2;1ko, were described elsewhere (Da Ines et al, 2010;Péret et al, 2012;Prado et al, 2013). The former is a pip2;1-1 mutant allele transformed with the PIP2;1 genomic sequence (Péret et al, 2012); the latter is a pip2;1-2 mutant overexpressing a PIP2;1 cDNA under the control of a double enhanced cauliflower mosaic virus 35S promoter (Prado et al, 2013).…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…Each of these PIPs ranks among the three most highly expressed isoforms in at least one previous gene or protein expression study of Arabidopsis leaves (Alexandersson et al, 2005;Monneuse et al, 2011). T-DNA insertion lines corresponding to knockouts for each of these PIPs in a Columbia-0 (Col-0) (PIP1;2, PIP2;1, and PIP2;6) or Landsberg erecta (Ler) (PIP2;7) background were available from previous studies (Da Ines et al, 2010;Postaire et al, 2010;Péret et al, 2012) or were molecularly characterized in this work (see Supplemental Figure 2 online). To evaluate Arabidopsis rosette aquaporin functionality, we previously established a method for measuring the K ros of internal rosette tissues.…”
Section: Contributions Of Individual Pip Genes To Rosette Water Transmentioning
confidence: 99%
“…The SALK_92140c (pip2;6-1) and SALK_118213c (pip2;6-2) Col-0 T-DNA insertion lines and the CSHL_GT19652 (pip2;7-1) Ler transposon insertion lines were obtained from the Nottingham Arabidopsis Stock Center and the Cold Spring Harbor Laboratory, respectively. Homozygous mutations and gene inactivation were verified by genotyping and RT-PCR (see Supplemental Figures 2 and 3 online) (Da Ines et al, 2010;Postaire et al, 2010;Péret et al, 2012) using the primers indicated in Supplemental Table 2 online. All procedures for plant genotyping were as described (Postaire et al, 2010).…”
Section: Transgenic Plant Materialsmentioning
confidence: 99%
See 1 more Smart Citation